Cardioprotective effects of enteral vs. parenteral lactoferrin administration on myocardial ischemia-reperfusion injury in a rat model of stunned myocardium - Keisuke Omiya; Yosuke Nakadate; Takeshi Oguchi; Tamaki Sato; Toru Matsuoka; Masako Abe; Akiko Kawakami; Takashi Matsukawa; Hiroaki Sato (BMC, 2022)
Abstract Background: Lactoferrin, an iron-binding glycoprotein, is known to have protective effects against intestinal and cerebral ischemia-reperfusion (IR) injuries; however, its cardioprotective effects against the stunned myocardium are unknown. This study aimed to test the hypothesis that lactoferrin has cardioprotective effects against stunned myocardium. Methods: Using isolated rat hearts (Langendorff system), we determined the effects of lactoferrin administered enterally and by direct cardiac perfusion. Rat hearts were perfused using the Langendorff system, and two experiments were performed. In experiment 1, the hearts were divided into the enteral lactoferrin (E-LF) 7.5 m, 15 m, 30 m, and 60 m groups, where lactoferrin (1000 mg/kg) was administered enterally 7.5, 15, 30, and 60 min, respectively, before perfusion; and a control group, where saline was administered 30 min before perfusion. In experiment 2, hearts were allocated to the perfusate lactoferrin (P-LF) 15 and 100 groups, where 15 mg/L and 100 mg/L lactoferrin were respectively added to the perfusate, and a control group. Each group was perfused for 20 min prior to 15 min of no-flow ischemia with pacing, followed by 20 min of reperfusion. The primary outcome was the maximum left ventricular derivative of pressure development (LV dP/dt max) 15 min after reperfusion. Myocardial phospho-protein kinase B (p-Akt) was assayed using western blotting. Results: The LV dP/dt max 15 min after reperfusion in the E-LF 15 and 30 m groups was significantly higher than that in the control group. However, the effects disappeared in the E-LF 60 m group. In the second experiment, there were no significant differences in LV dP/dt max. Myocardial p-Akt was not significantly activated in any lactoferrin group. Conclusion: Cardioprotection was observed 15-30 min after enteral lactoferrin but not by direct cardiac perfusion with lactoferrin. Myocardial p-Akt was not associated with the cardioprotective effect. The cardioprotective effect may be induced by enteral lactoferrin-induced substances.